Вплив іонізованого повітря на виробництво ячмінного солоду - Харитонова, Ганна Іванівна; Харитонова, Анна Ивановна; Kharytonova, Hanna; Олексієнко, Вадим Олександрович; Алексеенко, Вадим Александрович; Oleksiienko, Vadym (My University, 2019)
UK: Основним напрямом вдосконалення технології солодування є прискорення процесу і зниження затрат на виробництво солоду. Також розглянуті способи обробки зерна ячменю, які застосовуються в технології солодування. У статті описано і підібрано оптимальні режими опромінення ячменю і кратність. Визначено на якому етапі технологічного процесу слід проводити опромінення зерна – до замочування ячменю, після замочування або в процесі пророщування солоду. При цьому поставлено завдання домогтися максимального ефекту при збереженні простоти технічного рішення і мінімум витрат. RU: основным направлением совершенствования технологии солодоращения является ускорение процесса и снижение затрат на производство солода. Также рассмотрены способы обработки зерна ячменя, применяемые в технологии солодоращения. В статье описаны и подобраны оптимальные режимы облучения ячменя и кратность. Определили, на каком этапе технологического процесса следует проводить облучение зерна - до замачивания ячменя, после замачивания или в процессе проращивания солода. При этом ставилась задача добиться максимального эффекта, сохранив простоту технического решения при минимуме затрат. EN: The main trend in malting technology advancement is forcing of the process and cutting down the expenditures for malt production. Ways of barley grain treatment used in malting technology have also been considered. Optimal regimes of barley radiation and their order have been selected and descibed. We have determined the stage of technological process at which the grain should be exposed to radiation – before the soaking of barley in the water, after the soaking or in the process of malt germination. We aimed at receiving the maximum effect while preserving the simplicity of technical decision and minimizing expenditures. In order to select the best modes of irradiation of barley on the experimental plant, several options were studied, which differ in exposure and multiplicity of ionization. In this case, we used three versions of the degree of ionized air - 5, 10 and 15 minutes. When developing the mucilage technology using ionized air treatment, it was important to determine at what stage of the process the ionization of the grain should be carried out - to soak the grain, after soaking or in the process of mowing the malt. At the same time, they set the task to maximize the effect, maintaining the simplicity of the technical solution at a minimum cost. Initially, the effectiveness of ionized air on dry grain was detected. The study of the influence of ionized air on the ability of barley to germinate showed the inappropriate use of ionization by negative ions of oxygen to soaking the grain, since none of the doses of ionization applied to the air did not lead to a reliable picking of the similarity of barley with one-time irradiation of dry grain. Data on the effects of different doses of ionized air on these indicators are presented in Table 1. From the data of the table, it is seen that the supply of negative oxygen ions in exposures of 5 and 15 minutes gave an inadequate effect and revealed inhibition of the processes of barley germination. Only one irradiation had a positive effect on mosquito breeding - 10 minutes. In this variant, the rate of germination of barley sprouts is higher than the control index by 26.3%. Thus, we can talk about the positive effect of ionized air as a factor that allows us to prove the value of germination rates of barley to the standard condition.
Влияние ионизированного воздуха на производство ячменного солода
Influence of ionized air on the barley malt production
Keywords: солод; стимуляція; паростки; дозрівання солоду; оптимальні режими; іонізація; ефективність